Socializing the Importance of Scientific Writing for Undergraduate Students - Prasetyo, Dodi Erwin; Hadi, Abdul; Mahsuni, Abdul Wahid; Ulfiandi, Ihsan Zikri (Abdimas Indonesian Journal, 2025)
Research writing is by rehearsal. Hence, this paper aimed at discussing the importance of research writing for undergraduate students. This papers employed library research where the data were gathered from journal, articles, books and so forth. The finding asserted that research writing is important to extend students’ knowledge, experiences, and research partners. The advices are bestowed for students, lecturers, and curriculum makers. For students, it is required for their study fulfilments and extend knowledge. For lecturers, it is to trait and enhance students’ knowledge toward research writing and to gain more experiences within. For curriculum makers, it is needed to integrate scientific writing as obligation lesson for undergraduate students to advance their proficiency. Additionally, it is needed more deeper research and discussion for future research on how research writing affect students proficiency levels based on their study fields.